Couple‐based interventions for improving dyadic adjustment in people with cancer and their spousal partners - Liu, Yu‐Chen (Cochrane Database Syst Rev, 2019)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: (1) To evaluate the immediate and follow‐up effects of CIIDA at the dyad level among couples with a cancer diagnosis at six‐month intervals within one year of intervention compared to controlled status (no intervention, usual care, or alternative programmes); and (2) to identify the moderators of CIIDA that promote improvement in the dyadic adjustment of couples.